IMPLEMENTASI ALGORITMA FUZZY MAMDANI DAN FISHER-YATES SHUFFLE PADA GAME CITY STREET RUN - Sipayung, Evasaria Magdalena; Chandra, Kelvin (Jurnal Algoritma, Logika dan Komputasi, 2024)
This City Street Run game is made by taking a city street background and characters running to collect coins and pass obstacles to get the highest score. The character will run through object obstacles in the form of orange cones and red barriers while collecting coins which will affect the player's score. The reason the author makes this game is that it is expected to improve thinking power, improve concentration, solve problems and improve brain memory. This study uses the Mamdani Fuzzy Algorithm because this algorithm can make scores affect the character's running speed. Then this research also uses the Fisher-Yates Shuffle Algorithm so that coins can be spawned randomly in the City Street Run game. As well as implementing the Multimedia Development Life Cycle Method for the City Street Run game because the City Street Run game combines text, images and audio. Based on the test results with Black Box Testing, it can be concluded that all the features contained in the City Street Run game have run as expected and based on the test results with User Acceptance Testing through a questionnaire, with a percentage value of 85.5%, so it can be concluded that the City Street Run game is classified as very good and can be accepted and played by users. Based on these results, it can be concluded that the design of the City Street Run game was successfully implemented using the Multimedia Development Life Cycle method, the fuzzy mamdani algorithm and the Fisher-Yates Shuffle algorithm.